Analisis Kompensasi, Pendidikan dan Senioritas Terhadap Produktivitas Kerja Pegawai - Hendri Hendri; Lukman T Ibrahim; Yunida Pangastuti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
This study aims to determine the effect of partial and simultaneous variables of compensation, education, and seniority on employee productivity at the Office of Community Empowerment and Aceh Village. The object of this study were all apparatuses (employees) at the Office of Community Empowerment and Aceh Village. The number of respondents was determined by 81 employees using the census method. Data collection was carried out through interviews guided by a questionnaire. Methods of data analysis using multiple linear regression and using the t test and F test. The results of the study based on the results of the F-test (simultaneous) showed that all the variables studied had a significant effect on increasing employee productivity in the Office of Community Empowerment and Gampong Aceh with Fcount > Ftable, at the level of significance value a = 5%. As for the results of the t-test (partially), a very significant variable influencing employee productivity in the Office of Community Empowerment and Gampong Aceh is the compensation variable by obtaining a greater tcount than the education and seniority variables having a smaller t count.